Association between time spent on a cell phone, physical activity level, and academic performance in college students - Cigarroa, Igor; Fierro-Villarroel, Iván; Bravo-Leal, Michelle; Parra-Acevedo, María Paz; Guzmán-Muñoz, Eduardo; Tapia-Figueroa, Andrea; Zapata-Lamana, Rafael (Universidad y Salud, 2022)
Introduction: Low academic performance of college students has been associated with an increase in time spent on cell phones and a low physical activity. Objective: To analyze the relationship between time spent on cell phones, physical activity level, and academic performance in college students. Materials and methods: A study with a correlational and longitudinal temporality approach. During a semester, 36 college students were assessed on the time they spent using cell phones and their physical activity levels through the Moment and Pacer applications, respectively. Academic performance was monitored through report cards. Results: Men engaged in more physical activity and used cell phones more frequently during the analyzed period, while women showed higher physical activity levels and lower cell phone usage during evaluation periods (p=0.019 y p=0.033, respectively). Also, men who had better grade averages showed lower number of daily pickups (p=0.032). Conclusions: College men show higher physical activity levels and longer cell phone usage during the semester, while women tend to be more active and use their cell phones less frequently during evaluation periods. College students who use cell phones less regularly also have a better academic performance.